(untitled) (International journal of artificial intelligence, 2024)
Cognitive processes play a crucial role in second language acquisition (SLA), influencing how learners perceive, interpret, and internalize new linguistic structures and vocabulary. Understanding these processes sheds light on the mental mechanisms that underpin language learning, including attention, memory, perception, and problem-solving. The interaction between cognitive functions and language input is vital, as it determines how effectively learners can assimilate new information and apply it in real-world contexts. This introduction explores the key cognitive theories relevant to SLA, such as the Interaction Hypothesis, the Output Hypothesis, and the role of working memory. By examining these cognitive frameworks, we can gain insights into the strategies that enhance language learning and the challenges that learners face. Ultimately, this exploration aims to contribute to more effective pedagogical approaches that align with the cognitive realities of language acquisition.